Improving Social Studies Learning Outcomes Using PBL-Based Animated Videos in Elementary Schools - Irmawati D Ishak; Paramita Tahalu (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
The purpose of this study was to improve student learning outcomes in social studies using animated video moves based on the Problem Based Learning Model in Class V SDN 3 Mootilango, Gorontalo District. With the formulation of the problem whether the use of Problem Based Learning-based animated video can improve student learning outcomes in class V social studies subjects at SDN 3 Mootilango, Gorontalo District. Research subjects in Classroom Action Research (PTK) were students of class V with a total of 13 students consisting of 10 male students and 3 female students. And the main target in this study is to improve student learning outcomes in social studies subjects. The results of this study indicate an increase in the ability of students in completing assignments and evaluation questions both at each meeting and each cycle. This is shown in the learning outcomes of students who achieved learning completeness in the first cycle of learning completeness reached 62%, and at the second meeting it reached 77% and at the third meeting it increased to 93%. And it has exceeded the expected performance indicators.